Validation of the Pretreatment Neutrophil-Lymphocyte Ratio as a Predictor of Overall Survival in a Cohort of Patients With Pancreatic Ductal Adenocarcinoma. Issue 3 (April 2015) - Ben, Qiwen; An, Wei; Wang, Lifu; Wang, Weiyi; Yu, Lei; Yuan, Yaozong
Abstract : Objectives: The circulating neutrophil-lymphocyte ratio (NLR) has been shown to be a prognostic factor for a variety of tumors. In this study, we evaluated the prognostic significance of NLR in a large cohort of Chinese patients with pancreatic ductal adenocarcinomas (PDACs). Methods: A total of 381 patients with PDAC who underwent potentially curative surgery were recruited from 2 centers in Shanghai, China, between January 2004 and September 2011. Analysis of overall survival (OS) was performed using the Kaplan-Meier and log-rank tests and the Cox proportional hazards regression model. Results: The most optimal cutoff of NLR was NLR 2.0 or greater, and the NLR was divided into 2 groups: high (≥2.0) and low (<2.0). The high NLR (≥2.0) was associated with advanced UICC (Union for International Cancer Control) stages, p T stage, lymphoid node invasion, and poorer tumor differentiation. Multivariate analysis identified increased NLR as an independent prognostic factor for OS (hazard ratio = 1.51; 95 % confidence interval, 1.15–1.99; P = 0.003). Furthermore, neutrophil counts rather than lymphocyte counts were associated with OS of PDAC. Conclusions: The pretreatment NLR is a simple and useful potential biomarker for OS in patients with PDAC after curative resection.